2019
DOI: 10.1016/j.nano.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of amorphous silica nanoparticles: Status and prospects

Abstract: Amorphous silica nanoparticles (SNPs) are widely used in biomedical applications and consumer products. Little is known, however, about their genotoxicity and potential to induce gene expression regulation. Despite recent efforts to study the underlying mechanisms of genotoxicity of SNPs, inconsistent results create a challenge. A variety of factors determine particle-cell interactions and underlying mechanisms. Further, high-throughput studies are required to carefully assess the impact of silica nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 214 publications
0
36
0
4
Order By: Relevance
“…The human body can be exposed to aSiNPs through several routes such as inhalation, oral ingestion, transdermal penetration and parenteral injection intentionally or unintentionally. 6 In the last two decades, numerous studies in vivo and in vitro have evaluated the toxicity and biosafety of aSiNPs, and have demonstrated its potential adverse effects on human health. Several researches in vivo showed that after entering the experimental animal body, aSiNPs could distribute in almost all organs, and cause inflammation as well as tissue damage through direct or indirect ways.…”
Section: Introductionmentioning
confidence: 99%
“…The human body can be exposed to aSiNPs through several routes such as inhalation, oral ingestion, transdermal penetration and parenteral injection intentionally or unintentionally. 6 In the last two decades, numerous studies in vivo and in vitro have evaluated the toxicity and biosafety of aSiNPs, and have demonstrated its potential adverse effects on human health. Several researches in vivo showed that after entering the experimental animal body, aSiNPs could distribute in almost all organs, and cause inflammation as well as tissue damage through direct or indirect ways.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the effects of the NMs on DNA integrity we have employed the comet assay, a widely used test to assess genotoxicity of NMs [23,43]. Most of the in vivo instillation and inhalation studies for aSiO 2 NMs available in the literature report negative outcomes in terms of genotoxicity [4,13,36,57]. Y. Guichard, et al [4] showed that three consecutive intratracheal instillations of SiO 2 NPs (NM-200, NM-201, NM-202, and NM-203) at doses of 3, 6, or 12 mg/kg did not induce any signi cant primary and oxidative DNA damage in the rat lung.…”
Section: Discussionmentioning
confidence: 99%
“…In ammation and oxidative stress are two common hallmarks of NMs exposure that can lead to potential induction of DNA damage [42,43,57]. Based on Affymetrix analysed data, we decided to explore the expression of several genes involved in in ammation and stress response following in vivo NMs exposure using a Custom TaqMan Array 384-well micro uidic Cards (TAC).…”
Section: Gene Expression Alterations In the Rat Lung Tissue -Tac Analmentioning
confidence: 99%
“…Further studies on the safety in human, reproducibility, stability and scalability of the silica nanoparticles are expected. Numerous studies reported the toxicity profiles of silica nanoparticles in vitro cells or animal models [140][141][142][143][144][145]. However, to date, only one study confirmed that silica nanoparticles are safe in healthy humans [129].…”
Section: Potential For Future Researchmentioning
confidence: 99%